Perlindungan Hukum Terhadap Pelaku Usaha Melalui Sistem Cash on Delivery Pada Marketplace - I Gede Vera Yudana; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2022)
The use of information and electronic technology also plays an important role in trade and national economic growth to realize people's welfare. Such as trading activities that utilize information and electronic technology known as the Marketplace. Various types of payment systems have been provided on the Marketplace, one of which is the payment system through Cash On Delivery (COD). In practice, business actors who provide the COD method often experience defaults by buyers, to the detriment of business actors. Therefore, this study examines how valid the sale and purchase agreement through the COD system on the Marketplace? and how is the legal protection of business actors in the event of default through the COD system on the Marketplace?. This research uses a normative type of research. Providing legal protection to commercial actors aims to provide justice to parties affected by default. So in this case it is necessary to pay attention to the feasibility of sanctioning parties who do not use the COD method.